2016
DOI: 10.1111/aogs.12941
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte competence in in vitro fertilization and intracytoplasmic sperm injection patients suffering from endometriosis and its possible association with subsequent treatment outcome: a matched case–control study

Abstract: Endometriosis patients, in particular those with severe endometriosis, present lower-quality oocytes. Once fertilized, no impairment of further preimplantation embryo development and pregnancy outcome right up to healthy live birth rate has to be expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 37 publications
3
42
0
2
Order By: Relevance
“…Advanced maternal age also results in an increase of oocyte chromosomal abnormalities, which leads to a decline in the oocyte quality and dysontogenesis [6]. Diseases, such as moderate to severe endometriosis, decrease the ovarian reserve function, affect the oocyte quality and embryo development [7]. Several studies have demonstrated, short protocol may result in fewer number of oocytes retrieved and fewer good quality embryos [8,9], which may be a reason why rate of no good quality embryos was highest in the short protocol group.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced maternal age also results in an increase of oocyte chromosomal abnormalities, which leads to a decline in the oocyte quality and dysontogenesis [6]. Diseases, such as moderate to severe endometriosis, decrease the ovarian reserve function, affect the oocyte quality and embryo development [7]. Several studies have demonstrated, short protocol may result in fewer number of oocytes retrieved and fewer good quality embryos [8,9], which may be a reason why rate of no good quality embryos was highest in the short protocol group.…”
Section: Discussionmentioning
confidence: 99%
“…However, Pop-Trajkovic et al [15] found a negative correlation between the LBR in IVF-ICSI and the severity of endometriosis. Moreover, Shebl et al [16] showed that endometriosis rAFS stage IV was associated with significantly worse-quality oocytes than stages I-III (p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Частота его встречаемости среди пациенток, страдающих бесплодием, составляет до 35-50% [3]. Данная патология широко распространена, в том числе среди женщин репродуктивного возраста (до 15%) [19,21]. Эндометриоз -заболевание женской репродуктивной системы, при котором эндометрий разрастается за пределами матки.…”
Section: © коллектив авторов 2018unclassified
“…В нормальных условиях шпиндельное устройство ооцита должно быть компактным, образованным дискретными шпинделями, основным структурным компонентом которых является димер, со-стоящий из субъединиц α-и β-тубулина. Нарушение мейотического шпинделя приводит к аномальным выравниванию, выделению гомологичных хромосом и оплодотворению [19]. В последнее время морфология шпинделя стала маркером качества ооцитов.…”
Section: Endometriosis and Oocytes (A Review)unclassified